Voices of People With Disabilities: Integrating Topic Modeling and Sentiment Analysis to Study Disability Discourse on Social Media - Richard K. Lomotey; Sandra Kumi; Christian Nyaku; Ralph Deters (IEEE Access)
People with Disability (PwD) are some of society’s marginalized and vulnerable groups. They are mostly disadvantaged because accessibility to communal structures and social services remains challenging. Sometimes, PwDs are misunderstood because not all disabilities are visible or outward, which makes it difficult to implement useful interventions for them. Thus, the voices of PwDs, as expressed freely on social media, must be studied to better understand the fundamental challenges they face. In this research, we analyze the comments expressed in Disability communities on Reddit in the last 5 years (from 2019 to 2024) to uncover the concerns and sentiments of PwDs. Comments were collected through the Reddit API from 4 Disability subreddits, namely r/ADHD, r/Blind, r/deaf, and r/disability. Overall, a total of 601,215 comments were extracted for analysis. We applied topic modeling algorithms, namely Latent Dirichlet Allocation (LDA), Non-negative Matrix Factorization (NMF), and two variations of BERTopic (BERTopic with K-means clustering and BERTopic with HDBSCAN clustering) on each subreddit’s comments to extract hidden topics. The NMF discovered 15 topics in the r/Blind and 20 topics in the r/deaf. Furthermore, related topics were merged into themes, and we discovered nine themes in both r/ADHD and r/Blind, eight themes in r/deaf, and seven themes in r/disability. Additionally, a pre-trained transformer, SiEBERT, was used to determine the sentiments for the themes in each subreddit. The themes discovered across at least two subreddits are Mobility, Diagnosis, Education, Assistive and Accessible Technology, Support, Disability Accommodations, and Relations. PwD with ADHD struggle with the effects of medications, household chores, sleep, attention span, and oversubscribing to online payment services. The PwD, who are visually impaired, feel alienated by society, struggle with public transit systems, have limited employment, and experience harassment. Those with difficulty hearing express trouble with hearing devices, educational materials, technological challenges, limited workplace accommodations, and bad treatment from people. Our research discussed the themes and provided recommendations where applicable.